Formulation and Characterization of Ibuprofen Solid Dispersions Using Native and Modified Starches (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Ibuprofen is an anti-inflammatory analgesic drug that is weakly water-soluble with a poor bioavailability.Objectives: The aim of this study is to formulate ibuprofen solid dispersions by solvent evaporation method using natural polymers (native cassava and genetically modified cassava (GMS), Cassava nanocrystal and corn starches) as possible hydrophilic carriers at varying weight proportions to optimize ibuprofen solubility and dissolution.Material and Methods: Solvent evaporation method was used to formulate the ibuprofen solid dispersions at different drug polymer ratios. The pure drug and solid dispersions were characterized using Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffractometer (XRD), particle size, and in vitro drug release.Results: Solid dispersions formulated with starch nanocrystals showed the highest solubility. All solid dispersions prepared with drug:polymer ratio 1:2 generally showed highest solubility. According to the FTIR, the chemical structure of ibuprofen remained intact in the amorphous solid dispersion, but the structure changed from crystalline to amorphous, according to the XRD and the DSC also confirmed this. The scanning electron microscopy showed the solid dispersions were more porous than the pure drug. Higher dissolution rate was observed with nanocrystal solid dispersions with T50 (time required for 50% of the medication to be released) between 1.8 and 4.1 minutes.Conclusion: This study has shown that using these natural polymers increased the solubility and dissolution rate of ibuprofen.